Decision Support Mechanism for Cellular Production System – Application of NSGA-II Meta-heuristic and TOPSIS Ranking - Khan, A. S.; Ullah, R. (The Nucleus, 2019)
Cellular arrangement is considered beneficial for the distribution of heavy workload, resource utilization and fast paced production. In such mechanisms, machines, tools and product features are classified into different cells. Such arrangement impacts the overall performance of system in the form of productivity and throughput. In current study, serial, parallel and tubular systems have been analyzed with multiple variants of each production system. The objective is to select variants on the basis of optimal production time, least cost and higher productivity. Two methods have been used owing to the complex and combinatorial nature of the problem. Initially, a modified version of Non Sorting Genetic Algorithm (NSGA-II) has been used to provide Pareto fronts where possible candidates for optimum solution have been presented. A Multi Attribute Decision Making (MADM) approach of Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) criteria has been used to select the best compromise of optimal result. The results show that the objectives of cost, time and productivity are in conflict with each other and a global solution cannot be attained against the optimal values of all objectives. Also, an increased productivity can be assured by reducing the total time with an increase in cost.